2021
DOI: 10.53063/synsint.2021.1224
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of low BN additive on densification and mechanical properties of hot-pressed ZrB2–SiC composites

Abstract: The incorporation of 1 wt% hexagonal BN (hBN) into ZrB2–30 vol% SiC could noticeably better the fracture toughness, hardness, and consolidation behavior of this composite. This research intended to scrutinize the effects of various amounts of hBN (0–5 wt%) on different characteristics of ZrB2–SiC materials. The hot-pressing method under 10 MPa at 1900 °C for 120 min was employed to sinter all designed specimens. Afterward, the as-sintered samples were characterized using X-ray diffractometry (XRD), field emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many efforts have been done to increase the oxidation resistance of diborides. These studies showed that the addition of SiC to ZrB2 greatly increases oxidation resistance at high temperatures [36][37][38][39][40][41][42][43]. Thermodynamic calculations of the oxidation of ZrB2-SiC composites showed that the formation of a SiC-rich layer, a Zr-rich oxidized layer and a SiC-depleted ZrB2 layer due to active oxidation of SiC decreased the oxidation rate [44].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been done to increase the oxidation resistance of diborides. These studies showed that the addition of SiC to ZrB2 greatly increases oxidation resistance at high temperatures [36][37][38][39][40][41][42][43]. Thermodynamic calculations of the oxidation of ZrB2-SiC composites showed that the formation of a SiC-rich layer, a Zr-rich oxidized layer and a SiC-depleted ZrB2 layer due to active oxidation of SiC decreased the oxidation rate [44].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, applying high pressures and elevated temperatures is necessary to obtain a fully dense ZrB 2 sample, which encourages the growth of grains and results in a significant decline in fracture toughness. To overcome such problems, several research works have suggested the selection of suitable consolidation techniques and/or activating the toughening and sintering mechanisms utilizing the addition of additives [6][7][8]. Among spark plasma sintering (SPS), pressureless sintering (PS), reactive hot pressing (RHP), and hot pressing (HP) [9,10], as the sintering techniques for the fabrication of UHTCs, the first one is a newly developed route that utilizes direct current pulsing and external mechanical pressure to densify the materials synchronously [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The ZrB 2 itself has high oxidation resistance because of adherent and dense oxide scale formation 16,17 . The resistance to oxidation also alters by the addition of other compounds.…”
Section: Introductionmentioning
confidence: 99%